Temporal Regulation of the Transformasome and Competence Development in Streptococcus suis - Zaccaria, Edoardo; Wels, Michiel; van Baarlen, Peter; Wells, Jerry M. (Frontiers in Microbiology, 2016)
In S. suis the ComX-inducing peptide (XIP) pheromone regulates ComR-dependent transcriptional activation of comX (or sigX) the regulator of the late competence regulon. The aims of this study were to identify the ComR-regulated genes and in S. suis using genome-wide transcriptomics and identify their function based on orthology and the construction of specific knockout mutants. The ComX regulon we identified, includes all homologues of all the ‘transformasome’ a type 4-like pilus DNA binding and transport apparatus identified in S. pneumoniae, S. mutans and S. thermophilus. A conserved CIN-box (YTACGAAYW), predicted to bind ComX, was found in the promoters of operons encoding genes involved in expression of the transformasome. Mutants lacking the major pilin gene comYC were not transformable demonstrating that the DNA uptake pilus is indeed required for competence development in S. suis. Competence was a transient state with the comX regulon shut down after approximately 15 min even when transcription of comX had not returned to basal levels, indicating other mechanisms control the exit from competence. The ComX regulon also included genes involved in DNA repair including cinA which we showed to be required for high efficiency transformation. In contrast to S. pneumoniae and S. mutans the ComX regulon of S. suis did not include endA which converts the transforming DNA into ssDNA or ssbA, which protects the transforming ssDNA from degradation. EndA appears to be essential in S. suis so we could not generate mutants and confirm its role in DNA transformation. Finally, we identified a putative homologue of fratricin, and a putative bacteriocin gene cluster, that were also part of the CIN-box regulon and thus may play a role in DNA release from non-competent cells, enabling gene transfer between S. suis pherotypes or S. suis and other species.